Tradition as muse : Schoenberg's musical morphology and nascent dodecaphony - Heneghan, Áine (Trinity College (Dublin, Ireland). Department of Music, 2006)
This study reappraises the evolution of Arnold Schoenberg's method of composing with twelve tones by examining the interrelationship of his theoretical writings and compositional practice. Premised on the idea that theory and practice were interdependent for Schoenberg, I argue, on the one hand, that the richness and diversity of his nascent dodecaphony can be fully appreciated only in the context of the development of his musical thought and, on the other hand, that his terminological concepts—for example, Grundgestalt, 'unfolding' [Abwicklung], the distinction between Satz and Periode (sentence and period), and the differentiation of 'stable' and 'loose' construction—came about precisely because of his compositional experiments during the early 1920s. The discussion and musical analyses of selected movements from the Klavierstücke, Op. 23, the Serenade, Op. 24, and the Suite für Klavier, Op. 25, in chapters 3, 4, and 5 are preceded, in chapter 1, by a reassessment of Schoenberg's understanding of his musical tradition and, in chapter 2, by a survey of his changing compositional philosophy between 1909 and 1925. I contend that Schoenberg's re-engagement with the music of the past c. 1917 enabled him to deepen his understanding of tonality and sharpen his awareness of the qualities required by its replacement. Moreover, I show that it was this renewed interest in the past that led to a reconception of tonality: specifically, it was the Gedanke or musical idea—along with its associated laws, principles, and methods—that facilitated the emergence of dodecaphony, presenting itself as the necessary 'key' for unlocking the manifold possibilities of dodecaphony. Contrary to the one-dimensional portrayals of his Formenlehre (theory of forms) and the continued emphasis on motivicization, I aim to highlight the multi-faceted nature of Schoenberg's musical morphology. I, therefore, draw attention in his writings—and in those of his associates (including Anton Webern, Alban Berg, Erwin Stein, Josef Rufer, Erwin Ratz, Hanns Eisler, Leopold Spinner, and Philip Herschkowitz)—to the contrasting principles of polyphony and homophony, showing that one of the tenets of Schoenberg's theory of musical form was the intimate relationship between the technique of motivic presentation and resulting form. Further, I demonstrate that this bifurcation, which formed the basis of Schoenberg's unique conception of music history, was vital to his understanding of his own place in the Austro-Germanic musical tradition, in that his incipient dodecaphony perpetuated the cycles of musical evolution that he identified in the music of the past. In summary, I propose that, for Schoenberg, the abandonment of tonality precluded the composition of large-scale homophonic form (hence, in the period from 1909 to 1923, the prevalence of text-based pieces and shorter non-developmental forms often labelled Charakterstücke), and that his compositions between 1920 and 1923 were characterized by a multiplicity of techniques and practices. The principle of juxtaposition, which formed the basis of the paratactic structures and theme-and-variation forms of movements from Opp. 23 and 24, was superseded by the so-called 'new polyphony'—exemplified by the 'Präludium' from the Suite für Klavier—and the emerging emphasis accorded to rhythm as a constructive element. Finally, through a detailed analysis of the 'Menuett' from the Suite für Klavier, I argue that the formulation of dodecaphony can be understood in relation to Schoenberg's changing conception of the row, something that facilitated the reincorporation of 'developing variation' and the recapturing of large-scale homophonic form.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin